The Influence of the Discovery Learning Model on Students' Mathematical Problem-Solving Ability - Nurjanah, Egi Annisa; Sampoerno, Pinta Deniyanti; Hidajat, Flavia Aurelia (Dinasti International Journal of Education Management and Social Science, 2025)
These findings are useful for evaluating the impact of the Discovery Learning (DL) model on students' mathematical problem-solving skills. This was conducted using a Systematic Literature Review (SLR) approach. Of the 30 articles found, 19 were selected based on topic relevance and publication years 2021–2025. The findings demonstrate that the use of problem-solving models has a positive impact on students' analytical skills, conceptual understanding, learning interest, creativity, and activeness. Combined with learning media, tailored to learning styles, and considering student characteristics such as resilience and personality, DL increases its effectiveness. Furthermore, recent research shows that DL is relevant for application across various teaching materials and educational levels. Furthermore, DL has the ability to overcome the shortcomings of conventional approaches, which tend to be passive. Therefore, Problem Solving Skills can be used as a useful alternative teaching module to help students acquire mathematical skills appropriate to the modern era.